PENINGKATAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH MELALUI RINTISAN BANK SAMPAH RW. 06 KELURAHAN ARJOWINANGUN KOTA MALANG - Aan Fardani Ubaidillah; Melani Albar; Wiwit Suwargianto; Ifa Nurhayati (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
This community service is implemented in RW. 06 Cempaka Putih Puri Arjowinangun District of Kedungkandang Malang City. Initial condition of citizen RW. 06 still can not manage the garbage well. With regard to the condition, the participation of citizens in the management of garbage through the pioneering garbage bank is carried out with the purpose of the community to understand the principles of garbage management and concern for environmental health Increased. There are two approaches that authors use in the stub of garbage banks, namely Apreciative Inquiry and Working Out Loud. Both approaches are then described in the four stages of implementation of the program, namely Phase 1 (14-26 October 2018): Program planning, Phase 2 (27 October 2018): Socialization of environmental health, Phase 3 (28 October – 9 November 2018): Planning and Garbage Bank arrangement, and Phase 4 (10 November 2018): Socialization and inauguration of trash Bank. From the 4 stages of implementation of activities that have been applied, it can be concluded that the pioneering garbage bank can increase the participation of residents in the waste management of RW residents. 06 Kelurahan Arjowinangun, Kecamatan Kedungkandang Malang City.